Identifying gaps in the ex situ conservation of native plant diversity in China. (June 2023) - Ye, Jianfei; Shan, Zhangjian; Peng, Danxiao; Sun, Miao; Niu, Yanting; Liu, Yun; Zhang, Qian; Yang, Yong; Lin, Qinwen; Chen, Jin; Zhu, Renbin; Wang, Yingwei; et al.
Abstract: Due to intensified human pressure and climate change, ex situ conservation measures have become essential for conserving Earth's remaining biodiversity, but the development of targeted ex situ conservation strategies based on conservation gaps analysis is often a major challenge. Here, we used a dated phylogeny including 95.70 % of the Chinese vascular genera and 1, 540, 695 species distribution records to identify ex situ conservation gaps in the tree of life and geographic space in China. We found that at least 41.70 % (12, 716 species) of all vascular plant species (30, 494 species), including 49.31 % (1715 species) of Chinese endangered species, are conserved in the botanic gardens. The results show that most species in ex situ collections are from eastern China and have been housed in botanic gardens in this region, whereas several plant diversity hotpots in the southwestern and northwestern regions are not well represented in ex situ conservation; only 12.67 % of the collection capacity of the Chinese botanic gardens is allocated to endangered species; there are 18 phylogenetic clusters of genera absent from the ex situ collections and the missing species are mostly from alpine or desert, mainly distributed in the Himalaya-Hengduan Mountains and northern Xinjiang. Therefore, we suggest that more collection capacity of China be devoted to endangered species particularly in the southwestern and northwestern regions. Our study provides quantified resources of targeted inventory and area for future ex situ conservation in China, and a fundamental protocol to invest the future achievement of local or global ex situ conservation. Highlights: Ex situ conservation measures have become essential for conserving Earth's remaining biodiversity. The development of targeted ex situ conservation strategies is often a major challenge. We present a fundamental protocol to invest the future achievement of ex situ conservation. Provides quantified resources of targeted inventory and area for future ex situ conservation in China. Our method can be applied to reveal local or global ex situ conservation bias comprehensively.